Quantitative ethnobotanical study of medicinal plants used by local communities in Chamla Valley, Buner District, Pakistan - Ullah, Nazim; Ullah, Barkat; khan, Muhammad Nauman; Kaplan, Alevcan; Dossou-Yovo, Hubert Olivier; Wahab, Sana; Iqbal, Majid (Ethnobotany Research and Applications, 2024)
Background: An ethnobotanical survey was conducted in Chamla Valley, District Buner, Khyber Pakhtunkhwa (Pakistan) to document the traditional medicinal knowledge held by indigenous people on local plant species. The study area has a diversified flora with a remarkable potential for ethnobotanical uses. However, ethnomedicinal studies to state such indigenous information lack. The present research is a contribution to fill in this gap of knowledge. Methods: Data were collected from different socio-ethnic groups including aged people, herbal practitioners, and well-known aged people in the study area. To state scientific knowledge, these data were quantitatively analyzed using various ethnobotanical indices such as the relative frequency of citation (RFC), the use value (UV), fidelity level (FL), informant consensus factor (ICF), data matrix ranking (DMR) and the informant consensus factor (ICF). Results: A total of 153 plant species belonging to 134 genera and 67 families were recorded in this study, showing the relevance of ethnomedicine in the community. Among all these species, 85% (57 families) were dicots whereas 10.4% of them (7 families) were monocots. Only 4.47% (3 families) and 1.49% (1 family) were Pteridophytes and gymnosperms respectively. With regards to the types of the recorded plant species, herbs were predominant followed by shrubs, trees, and climbers. The most used parts were leaves followed by the entire plant, stem, root, and fruit. Twenty major ailment groups were recorded, of which gastrointestinal disease showed the highest value, meaning the most relative importance whereas cardiovascular disease exhibited the lowest value. Fifteen alien plant species were identified and analyzed by using the EICAT impact assessment. Conclusion: This study is the first quantitative investigation that emphasized the traditional herbal medicines used for ethnopharmacological purpose in Buner District, Chamla Valley, with information such as the mode of application and the treated diseases as well as the relative importance of the recorded species. Outputs of this study are of great importance to motivate advanced pharmacological and phytochemical screenings useful in the pharmaceutical sciences serving human health. Keywords: Ethnobotany; Asteraceae, Indigenous communities; Human diseases, Herbal medicine